HOW WE LOOK AND ARE LOOKED BY THE IMAGES? CRITICAL STUDY OF VISUAL CULTURE ARTIFACTS - João Paulo Baliscei; Vinícius Stein (Editora da Universidade de Santa Cruz do Sul, 2015)
The intensity with which the postmodern individuals relate to the visuality encourages us to reflect on the pedagogical ways of studying the cultural artifacts of everyday life, called artifacts of Visual Culture. In this article our aim is to investigate the similarities and convergences between Cultural Studies researches and Visual Culture Study regarding to visual artifacts studies. Thereunto, we developed a literature research where we discussed four perspectives that demonstrate pedagogical positions on the Visual Culture. In addition, we support on the self-reflexive perspective to study images and speeches offered by Barbie doll. In our considerations, we evidenced eight visual artifacts studies strategies that share with the principles of the quoted theoretical.